Te deum pour soli, choeur et orchestre - Delalande, Michel Richard 1657-1726 (Joyaux de la musique francaise, 1960)
Resumen: Symphonie--Petit choeur--Grand choeur--Duo (haute conte-bass) Grand choeur--Duo (2 sopranos)--Choeur--Récit (soprano)--Recit soprano)--Recit (basse)--Recit (haute-contre-Choeur--Recit et air (soprano)--Petit choeur--Grand choeur--Duo (soprano-haute-contre)--Trio (haute-contre-ténor-bass)--Choeur